1981
DOI: 10.1016/s0082-0784(81)80125-7
|View full text |Cite
|
Sign up to set email alerts
|

The thermal decomposition of pulverized coal particles

Abstract: The physical, thermal, and chemical behavior of pulverized coal particles during thermal decomposition are examined for five coal types and two particle sizes for one of the bituminous coals. Particles were injected axially into a lean (35% excess air) methane/air fiat flame with a nominal peak temperature of 1750~ The significant events observed are classified by three time scales. Particles heat to the gas temperature in less than 10 msec, devolatilization occurs between 10 and 75 msec and, under the appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 5 publications
3
45
0
Order By: Relevance
“…They suggested that energy from the oxidizing volatiles was fed back to the coal panicles, increasing their temperature and thereby the volatile release rate and yield. An increase of the particle temperature due to the oxidation of volatiles was also reported by Seeker et al (1981). Devolatilization rates and yields increase with panicle temperature have also been observed in experiments by Kimber and Gray ( 1967) (1973) suggested that oxygen complex fonnation at the surface and char activation may also be important at this early stage of conversion.…”
Section: High Temperature Conversionsupporting
confidence: 58%
“…They suggested that energy from the oxidizing volatiles was fed back to the coal panicles, increasing their temperature and thereby the volatile release rate and yield. An increase of the particle temperature due to the oxidation of volatiles was also reported by Seeker et al (1981). Devolatilization rates and yields increase with panicle temperature have also been observed in experiments by Kimber and Gray ( 1967) (1973) suggested that oxygen complex fonnation at the surface and char activation may also be important at this early stage of conversion.…”
Section: High Temperature Conversionsupporting
confidence: 58%
“…[16][17][18][19][20] This is supported by simple treatments of nucleation and growth of particles in a boundary layer. [21][22][23] More detailed treatment of nucleation in the boundary layer of a growing particle is presented by Peshty et al, 24 who show that the correct treatment should allow for heat release due to condensation, which tends to suppress the nucleation rate locally.…”
Section: Nucleation Versus Surface Growthmentioning
confidence: 86%
“…Soot formation in idealized flames and heat transfer by soot in boilers were also hot topics in combustion research (McLean et al 1981;Seeker et al 1981), resulting in many measurements of pure soot. Concurrently, a series of field experiments investigated the light-absorbing component of atmospheric aerosol in Denver, Colorado .…”
Section: History: How Did We Get Here?mentioning
confidence: 99%